Religion and politics in interwar Yugoslavia Serbian nationalism and East Orthodox Christianity - Falina, Maria (Bloomsbury Academic, 2023)
"The persistence of religion in modern Europe and the challenges of transitioning from a religious to a secular state has all too often been overlooked in the history of the Balkans. Indeed, the link between religion and nationalism in this region has long been considered natural, even historically inevitable. Religion and Politics in Interwar Yugoslavia challenges this assumption and shows that, in actuality, the region's political and spiritual identities clashed in a fashion that was just as important to the first South Slav state as the much vaunted 'national question' itself. Focusing on the interwar era, this book explores the role of the Serbian Orthodox Church in Yugoslavia. It examines the church's political vision and reveals how the Serbian Orthodox Church emerged both in reaction to and in interaction with the challenges posed by political modernity such as the establishment of the multinational Yugoslav state, the fear of secularization, and the rise of communism and fascism in Europe. Synthesizing analyses of ideologies and public discourses with stories of personal histories and individual agendas, Maria Falina's insightful study is therefore a significant contribution to the history of religion and nationalism in the Balkans."
Literaturverzeichnis: Seite [181]-199
Keywords: Serbisch-orthodoxe Kirche; Geschichte 1918-1941; Nationalismus; Jugoslawien; Nationalism / Yugoslavia; Nationalism / Serbia / History; History; History of religion; Yugoslavia / History / 1918-1945; Yugoslavia / Politics and government